Cerebral Autoregulation Is Disrupted Following a Season of Contact Sports Participation - Wright, Alexander D.; Smirl, Jonathan D.; Bryk, Kelsey; Fraser, Sarah; Jakovac, Michael; van Donkelaar, Paul (Frontiers in Neurology, 2018)
Repetitive subconcussive head impacts across a season of contact sports participation are associated with a number of deficits in brain function. To date, no research has investigated the effect of such head impact exposure on dynamic cerebral autoregulation (dCA). To address this issue, 179 elite, junior-level (age 19.6 ± 1.5 years) contact sport (ice hockey, American football) athletes were recruited for pre-season testing. 52 non-concussed athletes returned for post-season testing. 15 non-contact sport athletes (age 20.4 ± 2.2) also completed pre- and postseason testing. dCA was assessed via recordings of beat-by-beat mean arterial pressure (MAP) and middle cerebral artery blood velocity (MCAv) using finger photoplethysmography and transcranial Doppler ultrasound, respectively, during repetitive squat-stand manoeuvres at 0.05 Hz and 0.10 Hz. Transfer function analysis was used to determine Coherence (correlation), Gain (response amplitude), and Phase (response latency) of the MAP-MCAv relationship. Results showed that in contact sport athletes, Phase was reduced (p=0.027) and Gain increased (p<0.001) at post-season compared to pre-season during the 0.10 Hz squat-stand manoeuvres, indicating cerebral autoregulatory impairment in both the latency and magnitude of the response. Changes in Phase were greater in athletes experiencing higher numbers and severity of head impacts. By contrast, no changes in dCA were observed in non-contact sport controls. Taken together, these results demonstrate that repetitive subconcussive head impacts occurring across a season of contact sports participation are associated with exposure-dependent impairments in the cerebrovascular pressure-buffering system capacity. It is unknown how long these deficits persist or if they accumulate year-over-year.